Enzyme-Free Electrochemical Sensors for in situ Quantification of Reducing Sugars Based on Carboxylated Graphene–Carboxylated Multiwalled Carbon Nanotubes–Gold Nanoparticle–Modified Electrode - Liu, Ke; Wang, Xiaodong; Luo, Bin; Wang, Cheng; Hou, Peichen; Dong, Hongtu; Li, Aixue; Zhao, Chunjiang (Frontiers in Plant Science, 2022)
The reducing sugars of plants, including glucose, fructose, arabinose, galactose, xylose, and mannose, are not only the energy source of plants, but also have the messenger function of hormones in signal transduction. Moreover, they also determine the quality and flavor of agricultural products. Therefore, the in situ quantification of reducing sugars in plants or agriculture products is very important in precision agriculture. However, the upper detection limit of the currently developed sugar sensor is not high enough for in situ detection. In this study, an enzyme-free electrochemical sensor for in situ detection of reducing sugars was developed. Three-dimensional composite materials based on carboxylated graphene–carboxylated multi-walled carbon nanotubes attaching with gold nanoparticles (COOH-GR–COOH-MWNT–AuNPs) were formed and applied for the non-enzymatic determination of glucose, fructose, arabinose, mannose, xylose, and galactose. It was demonstrated that the COOH-GR–COOH-MWNT–AuNP-modified electrode exhibited a good catalysis behavior to these reducing sugars due to the synergistic effect of the COOH-GR, COOH-MWNT, and AuNPs. The detection range of the sensor for glucose, fructose, arabinose, mannose, xylose, and galactose is 5–80, 2–20, 2–50, 5–60, 2–40, and 5–40 mM, respectively. To our knowledge, the upper detection limit of our enzyme-free sugar sensor is the highest compared to previous studies, which is more suitable for in situ detection of sugars in agricultural products and plants. In addition, this sensor is simple and portable, with good reproducibility and accuracy; it will have broad practical application value in precision agriculture.